2006
DOI: 10.1103/physrevb.74.205422
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic exchange effects on the radiative decay time of monoexcitons and biexcitons in quantum dots

Abstract: Electron-hole exchange interactions split the exciton ground state into "dark" and "bright" states. The dynamics of those states depends on the internal relaxation time between bright and dark states (spin-flip time), and on the radiative recombination time of the bright states. On the other hand, the calculated values of these recombination times depend not only on the treatment of correlation effects, but also on the accuracy of the electron and hole wavefunctions. We calculate the radiative decay rates for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
54
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 21 publications
9
54
0
Order By: Relevance
“…These calculations are in perfect agreement with timeresolved experiments performed in QDs ensemble [5] and in single QDs [6] where capture times of the order of 100 ps have been measured. On the other hand, irreversible Auger scattering is mainly responsible for the intra-dot relaxation process, and theoretical calculations [1,7] give estimate of the corresponding relaxation times in the 100 fs -10 ps range. In fact, differential transmission measurements [8], pump-probe spectroscopy [9] and time-resolved experiments [10,11] showed that the Auger-assisted processes involved in the intra-dot carriers relaxation occur within characteristic times between 1 ps and 10 ps.…”
Section: Introductionmentioning
confidence: 99%
“…These calculations are in perfect agreement with timeresolved experiments performed in QDs ensemble [5] and in single QDs [6] where capture times of the order of 100 ps have been measured. On the other hand, irreversible Auger scattering is mainly responsible for the intra-dot relaxation process, and theoretical calculations [1,7] give estimate of the corresponding relaxation times in the 100 fs -10 ps range. In fact, differential transmission measurements [8], pump-probe spectroscopy [9] and time-resolved experiments [10,11] showed that the Auger-assisted processes involved in the intra-dot carriers relaxation occur within characteristic times between 1 ps and 10 ps.…”
Section: Introductionmentioning
confidence: 99%
“…Even in much larger, selfassembled InGaAs/GaAs dots, the spacing between the electronic levels (∼50 meV) is larger than the LO phonon energy (∼30 meV). [13][14][15][16] When the spacing between electronic levels exceeds the phonon energy, one would expect [5,6] under the adiabatic approximation [17] no phonon-assisted relaxation, on account of the unavailability of energy-conserving phonons. This scenario led to the expectation [4,5] of slow intra-band relaxation of high-energy states in quantum dots [ Fig.…”
mentioning
confidence: 99%
“…6,7 This is close to values determined by other techniques [14][15][16] and predicted by theory. 17 The capture time c , whose value was checked not to play an important role, was fixed to 10 ps. This is also in the range of capture times reported by other authors.…”
Section: Results and Calculationsmentioning
confidence: 99%